(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
This article discusses the role of music and the science of music in human life in Islam, the specific views of religious leaders, scholars and hadith scholars, the attitude to music and poetry, discussions and debates on the example of narrations and hadiths.